THE USE OF MOODLE BY CADETS OF MILITARY HIGHER EDUCATION INSTITUTIONS IN THE PROCESS OF SELF-STUDY WHEN LEARNING A FOREIGN LANGUAGE - Sovhar, Оксана; Boichenko, Вікторія (Journal of Information Technologies in Education (ITE), 2022)
The article tackles the problem of self-study organization of future officers of the Armed Forces of Ukraine in the context of a foreign language learning. Self-study is considered as an important factor of self-education and educational and cognitive activity of cadets. Forms and means, as well as types of self-study are analyzed and ways to improve the process of a foreign language mastering by optimizing the activities of cadets during self-education using the learning management system Moodle are suggested. It has been determined that self-education of future officers of the Armed Forces at a foreign language studying using LMS Moodle contributes to the acquisition of important skills, including analysis of foreign language professionally oriented texts, obtaining the necessary information, evaluation and application of available information for effective combat missions completion and interaction in foreign language. It has been established that the readiness level of cadets to perform self-education increases when it is a holistic course, developed on the basis of methodically organized educational information environment. Among the benefits of the Moodle learning management system, which implements the philosophy of “pedagogy of social constructivism”, is primarily the effective organization of interaction between teacher and cadets. Designing educational processes using presented approaches to introduce and practise educational content with Moodle significantly increases the learning effectiveness, simplifies the perception of educational material, enhances motivation to learn a foreign language and has a positive effect on its effectiveness.